Ultrasonographic Measurement of Optic Nerve Sheath Diameter in Patients with Traumatic Head Injury: A Prospective Observational Study - Ghimire, Niraj; Paudel, Nabin; Ghimire, Nisha; Ghimire, Prasanna; Koirala, Asmit (Journal of Nepalgunj Medical College, 2024)
Introduction: The early detection of elevated intracranial pressure is crucial for guiding interventions and improving patient outcomes in head injury patients. The intracranial pressure assessment with invasive intracranial devices is the gold standard. These devices however has a risk of infection, bleeding and dislodgement. Optic nerve sheath diameter measurement using ultrasonography has emerged as a promising method for indirect intracranial pressure estimation.Aims: To observe the changes in optic nerve sheath diameter over period of time, and to correlate the optic nerve sheath diameter with computed tomography findings of raised intracranial pressure in traumatic head injury.Methods: A prospective cross-sectional time series study was conducted at Nepalgunj Medical College to assess the utility of ultrasonography measurement of optic nerve sheath diameter in patients with head injuries from August 2023 to January 2024. Forty-nine patients with head injuries were included in the study. The ultrasonographic optic nerve sheath diameter measurements were obtained at admission, 48 hours post-admission, and 1 month post-head injury. The clinical parameters including Glasgow Coma Scale and radiological findings from Computed Tomography head were recorded.Results: Forty nine patients were enrolled in the study. Among them, 44.90% (27) were male and 55.10% (22) were female. Age ranged from 5 to 66 years, with a mean of 33.94 ± 15.27 years. The mean optic nerve sheath diameter was 5.24±0.86 mm at admission which decreased to 4.31±0.62 mm at 48 hours and 4.02±0.47 mm at 1 month. Our study showed significant reduction in optic nerve sheath diameter after conservative or surgical treatment in patients with head injury (F = 27.017; P =0.002) Conclusion: The ultrasonographic measurement of optic nerve sheath diameter proved to be a valuable tool in monitoring intracranial pressure in patients with head injuries.